2014
DOI: 10.3109/10903127.2013.864358
|View full text |Cite
|
Sign up to set email alerts
|

When Should You Test for and Treat Hypoglycemia in Prehospital Seizure Patients?

Abstract: Rates of hypoglycemia were very low in patients treated by EMS for seizure. Glucose testing prior to benzodiazepine administration significantly increased the median time to benzodiazepine administration. Given the importance of rapid treatment of seizure in actively seizing patients, measurement of blood glucose prior to treating a seizure with a benzodiazepine is not supported by our study. EMS seizure protocols should be revisited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The majority of pediatric patients undergoing blood glucose monitoring and receiving treatment for hypoglycemia in the prehospital setting have a chief complaint of seizure . In contrast, Beskind et al . found that hypoglycemia was a rare event in EMS calls for seizures (1.2%) when examining a combined adult and pediatric population.…”
Section: Goals Of This Investigationmentioning
confidence: 97%
“…The majority of pediatric patients undergoing blood glucose monitoring and receiving treatment for hypoglycemia in the prehospital setting have a chief complaint of seizure . In contrast, Beskind et al . found that hypoglycemia was a rare event in EMS calls for seizures (1.2%) when examining a combined adult and pediatric population.…”
Section: Goals Of This Investigationmentioning
confidence: 97%
“…There has been little agreement on when this testing should be performed since hypoglycemia can manifest as seizures, but checking blood glucose may delay the administration of benzodiazepines 12. While some protocols require checking blood glucose prior to the administration of benzodiazepines, others leave the timing to the discretion of the treating paramedic 4,12…”
Section: Evidence Review and Current Recommendationsmentioning
confidence: 99%
“…In a retrospective observational study of 53,505 EMS calls for seizure where blood glucose was measured, hypoglycemia was present in 638 (1.2%) patients with seizures 12. Seizing patients were treated with benzodiazepine in 8.3% and with glucose in 1.3% of patients.…”
Section: Evidence Review and Current Recommendationsmentioning
confidence: 99%
“…Although hypoglycaemia is an uncommon cause of SE, it is readily reversible . Glucose testing should not delay the administration of benzodiazepines …”
Section: Resultsmentioning
confidence: 99%
“…11 Glucose testing should not delay the administration of benzodiazepines. 37,38 Australasian pre-hospital protocols…”
Section: Blood Glucosementioning
confidence: 99%